(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2025)
Abstract: this article presents findings from research investigating the growth, development, and yield formation of soybeans, mung beans, and kidney beans when intercropped with cotton.